The Joint Effect of Organizational Characteristics, Governance Reforms, and Stakeholder Management on the Performance of Ports in Africa - Atonga, Joseph; Awino, Zachary; Ogollah, Kennedy; Odock, Stephen (Transactions on Engineering and Computing Sciences, 2025)
The key purpose of carrying out this research was to determine the joint effect of organizational characteristics, governance reforms, and stakeholders’ management on the operational performance of seaports from Africa. The research philosophy employed by the study was positivism with a descriptive cross-sectional census survey design. Structured questionnaires were deployed to collect primary data from 46 top executives of seaports in Africa that specialize in handling containers. The rate of response was response rate was 83%. Additional published data was also obtained from the websites of some of the ports. Reliability and validity for the indicator items were ascertained through diagnostic tests. Model fitness was ascertained by obtaining ratios of SRMR and NFI. Data analysis was carried out by Partial Least Squares Structural Equation Modelling (PLS-SEM) using Smart PLS4.1 software. PLS-SEM was also used to test the hypothesis that the joint effect of organizational characteristics, governance reforms, and stakeholders’ management on the operational performance of seaports from Anglophone Africa was not significantly greater than the individual effect of each variable on the performance. The individual effects of each variable with their moderating effects were the first to be determined through PLS-SEM before finally establishing the joint effect of the three exogenous constructs. The finding established that the joint effect was greater than the individual effect of each variable and concluded that a joint application of the three variables greatly improves the performance of seaports in Africa, thereby enabling them to gain a competitive advantage. The study adds to new knowledge, policy, and practice by enabling managers, policy makers and governments, and regulators to expand, plan, build, and operate new ports from an informed point of view.